How the Coronavirus Pandemic has Affected Gender Wage Inequality in Colombia - Héctor Alberto Botello-Peñaloza (Equidad & Desarrollo, 2021)
This article aims to compare how gender wage differences among Colombian workers have changed before and during the coronavirus pandemic. The parametric breakdown of Oaxaca-Blinder is performed based on microdata from the 2020 Large Integrated Household Survey and compared with the 2019 results. Among the results, the differential in hourly labor income against women has increased to 16% in 2020 versus 4% in 2019, especially in the lower part of the distribution. For both years and all income levels, most of the contribution to the gap is due to the unexplained part associated with discrimination. However, this effect is counterbalanced by women’s contributions, which are highly concentrated in the upper-income brackets.